Call to war - Blade, Adam (Blade, Adam. Chronicles of Avantia ;, 2012)
Tanner, his companions, and the Beasts continue their quest to retrieve the pieces of the Mask of Death, but Lord Derthsin's evil armies swarm over the land and his control over the people of Avantia continues to grow, until it seems that only the Beasts and their riders stand in his way.